2014
DOI: 10.2500/ajra.2014.28.3977
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Control in the Dual Diagnosis of Obstructive Sleep Apnea Syndrome and Rhinitis: A Prospective Analysis

Abstract: Our study showed a statistically significant positive correlation between clinical control of rhinitis symptoms and clinical control of OSAS. This study emphasizes the importance of achieving concurrent optimal control of both OSAS and AR/NAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Of interest, our findings for non-allergic rhinitis in adults were stronger in males than in females, which could be due to hormonal effects on immune responses or rhinitis, or to misdiagnosis of symptoms of sleep apnea as rhinitis in male adults. Obstructive sleep apnea (OSA) is a common comorbidity of obesity 34 or allergic rhinitis 35, 36 , and uncontrolled rhinitis can lead to OSA 37 . Although we lacked data from sleep studies in study participants, adjustment for symptoms of OSA (not considered in previous studies) did not change the association between obesity and non-allergic rhinitis in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, our findings for non-allergic rhinitis in adults were stronger in males than in females, which could be due to hormonal effects on immune responses or rhinitis, or to misdiagnosis of symptoms of sleep apnea as rhinitis in male adults. Obstructive sleep apnea (OSA) is a common comorbidity of obesity 34 or allergic rhinitis 35, 36 , and uncontrolled rhinitis can lead to OSA 37 . Although we lacked data from sleep studies in study participants, adjustment for symptoms of OSA (not considered in previous studies) did not change the association between obesity and non-allergic rhinitis in adults.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy with the previous studies may be attributed to different methodologies and the fact that there was a high prevalence of AR among our cohort patients. Interestingly, one recent study reported a significant positive correlation between clinical control of rhinitis symptoms and clinical control of OSA [ 23 ]. Although the effect of treating AR on the control of OSA was not addressed in our study, we reported a trend of a slightly increased AHI (not statistically significant) among patients with AR and OSA in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 12 of 45 of the patients with OSAS had the complication of allergic rhinitis; consequently, posterior nasal neurectomy may be effective for the management of these patients with allergy. 22…”
Section: Discussionmentioning
confidence: 99%